PENGARUH KESESUAIAN KOMPENSASI, PENGENDALIAN INTERNAL, DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (FRAUD) - Ni Nyoman Suwarianti; Ni Komang Sumadi (UNHI Press, 2020)
The purpose of this study is to prove the effect of compensation suitability, internal control, andcompliance with accounting rules for the tendency of accounting fraud (Fraud). The cooperative inKediri District, Tabanan Regency, which already has a legal entity, conducted this research.Triangele Teory and Teory Agency were used in this research. Withdrawal samples from thepopulation using a purposive sampling method with cooperative criteria that made respondents arelegal entities and still active who are aged over 10 years as many as 52 cooperatives. Thecooperative manager and head of the finance department were given a questionnaire in this study.Questionnaires are the method of this research. Multiple linear regression is the analytical toolused. The results show that the suitability of compensation, internal control and rule obedience havea negative effect on the tendency of accounting fraud, this can be proven as follows: (1.) suitabilityof compensation for the significant value of the t test of 0.007 <Î± = 0.05, tcount of 0.453 andregression coefficient (-0.258), thus H1 is accepted. (2.) Internal control significant value of t testis 0.005 <Î± = 0.05, tcount is 0.724 and regression coefficient (-0.051), thus H2 is accepted. (3.)obedience of accounting rules significant value of t test is 0.009 <Î± = 0.05, tcount is 0.096 andregression coefficient (-0.042), thus H3 is accepted.